The Effect of Benefits, Risks, and Trust on the Reuse of DANA Digital Wallet (E – Wallet) on the Surabaya City Community - Mochamad Rafi Kurniawan; Lia Nirawati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The digital era and its technology are growing, making conventional activities all digital, having an impact on human life, namely changes to the transaction system that can be done online. Various innovations created by human work aim to make their lives easier. At this time, people prefer to use digital wallets (e-wallet) on the devices they have, for example smartphones, so that reuse cannot be separated from the benefits of using, risks, and trust in digital wallets (e-wallet), especially DANA which is one of the The largest digital wallet in Indonesia. This research uses quantitative methods. The population in this study are DANA digital wallet (e-wallet) users in the city of Surabaya. The number of samples used is a number of 100 respondents using purposive sampling method. The data analysis technique used multiple linear regression analysis technique with the help of SPSS for windows version 26.0 calculator. The findings of this study indicate that: (1) The use of benefits has a positive and significant effect on the reuse of DANA's digital wallet (e-wallet) in the city of Surabaya. (2) The risk has a positive and significant impact on the reuse of DANA's digital wallet (e-wallet) in the city of Surabaya. (3) Trust has a positive and significant effect on the reuse of DANA's digital wallet (e-wallet) in the city of Surabaya. It can be concluded that the three independent variables (use benefits, risks, and trust) have a positive effect on the reuse of DANA's digital wallet (e-wallet) in the city of Surabaya.